2014
DOI: 10.1107/s2053230x14004166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different crystal forms of theMycobacterium tuberculosisESX-1 secreted protein regulator EspR

Abstract: The Mycobacterium tuberculosis ESX-1 secreted protein regulator (EspR, Rv3849) is the key protein that delivers bacterial proteins into the host cell during mycobacterial infection. EspR binds directly to the espACD operon and is involved in transcriptional activation. In the current study, M. tuberculosis EspR has been crystallized and its X-ray structure has been determined at 3.3 Å resolution in a P3221 crystal form. EspR forms a physiological dimer in the crystal. Each EspR monomer contains an N-terminal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The CapH CTD homodimer is stabilized by a hydrophobic core comprising Phe81, Tyr85, Leu96, and Leu100 of each protomer (Fig 3C). The CapH CTD homodimer resembles the C‐terminal dimerization domains of other dimeric bacterial transcription factors, including Mycobacterium tuberculosis EspR, Bacillus subtilis SinR, and Citrobacter C.Csp231I (Lewis et al , 1998; Gangwar et al , 2014; Shevtsov et al , 2015). The CapH CTD homotetramer is assembled through a separate hydrophobic interface between the C‐terminal α‐helices of four protomers, involving residues Ile99 and Phe103 (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…The CapH CTD homodimer is stabilized by a hydrophobic core comprising Phe81, Tyr85, Leu96, and Leu100 of each protomer (Fig 3C). The CapH CTD homodimer resembles the C‐terminal dimerization domains of other dimeric bacterial transcription factors, including Mycobacterium tuberculosis EspR, Bacillus subtilis SinR, and Citrobacter C.Csp231I (Lewis et al , 1998; Gangwar et al , 2014; Shevtsov et al , 2015). The CapH CTD homotetramer is assembled through a separate hydrophobic interface between the C‐terminal α‐helices of four protomers, involving residues Ile99 and Phe103 (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…2, Table S2), for it applies to the mycobacterial regulators KmsR (Campbell et al, 2007), ArgP (Zhou et al, 2010), BlaI (Sala et al, 2009) and EspR (Gangwar et al, 2014), which have all independently been confirmed to form homodimers in vitro.…”
Section: Distinguishing Monomeric From Dimeric Regulators In M Tubermentioning
confidence: 99%